EFL Instructors’ Perceptions on the Integration and Implementation of MALL in EFL Classes - Khan, Raja Muhammad Ishtiaq; Noor Raha, Mohd Radzuan; Shahbaz, Muhammad; Ainol Haryati, Ibrahim (Universiti Malaysia Pahang, 2018)
Mobile assisted language learning (MALL) has opened new opportunities for language instructors to develop and use handheld technology and implement new teaching practices focused on learners. The increased use of technology in language learning means instructors can play a key role in motivating learners by integrating readily available technologies for language learning development into their teaching practices. The focus of this present investigation is to explore the attitudes of Saudi instructors teaching English as a foreign language (EFL) regarding the implementation of mobile-assisted language learning (MALL). The target population for this study was EFL instructors who are currently teaching English in Saudi Arabia. The research methods for the study included a questionnaire, as well as in-depth interviews that were conducted to explore the attitudes of EFL instructors. The results of the questionnaire and interviews revealed moderately positive attitudes among participants regarding the use of mobile phones for language learning and teaching activities. The findings also indicate the existence of some challenges that could prove to be a significant hurdle for mobile phone integration in EFL learning and teaching in Saudi Arabia. Most of the instructors reported that they did not use mobile phones or MALL activities in their EFL classes. The results also showed that EFL teachers do not have the required skills to use/develop MALL activities. This study concludes by offering recommendations and suggestions for how to implement MALL and remove potential barriers to MALL implementation in EFL instruction.